Stakeholder interests and sharia compliance assurance: a discourse on the role of sharia boards of Islamic banks - Sheikh Hassan, Ahmad Fahmi (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
This study argues that the relevant theoretical framework underlying the operations of Islamic banks is the stakeholder theory with the stakeholders are expected to be ultimately concerned with the provision of Islamic banking products and services that are Sharia compliant. Based on our semi-structured interviews undertaken with 46 key players operating in the Sharia governance framework of the Malaysian Islamic banking industry, our study reveals only a weak emphasis for the stakeholder theoretical framework. We derive this conclusion based on our finding that Sharia boards are overwhelmingly inclined to limit themselves to aspects related to the development and approval of Islamic banking products. This study also reports that the Sharia compliance review is primarily undertaken by Islamic banks’ internal Sharia compliance officers, and then merely presented to the Sharia board for approval. Interestingly, the study further reports that the appointment of Sharia board members was predominantly motivated by a desire to image build and to serve the commercial interests of Islamic banks, thus raising concern that boards are being used as a tool for satisfying managerial opportunistic behaviour. Finally, the pursuit of stakeholder interest assumed by Islamic banks was reported to be influenced by conventional banking practice.